2010
DOI: 10.1016/j.jhep.2010.01.034
|View full text |Cite
|
Sign up to set email alerts
|

Differences in presentation and progression between severe FIC1 and BSEP deficiencies

Abstract: Background & Aims-Progressive familial intrahepatic cholestasis (PFIC) with normal serum levels of gamma-glutamyltranspeptidase can result from mutations in ATP8B1 (encoding familial intrahepatic cholestasis 1 [FIC1]) or ABCB11 (encoding bile salt export pump [BSEP]). We evaluated clinical and laboratory features of disease in patients diagnosed with PFIC, who carried mutations in ATP8B1 (FIC1 deficiency) or ABCB11 (BSEP deficiency). Our goal was to identify features that distinguish presentation and course of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
190
3
4

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 180 publications
(202 citation statements)
references
References 42 publications
5
190
3
4
Order By: Relevance
“…17,18 As also seen in the present study, PFIC 3 presents relatively late with cholestatic symptoms developing in late infancy (1/3rd) to adolescent age group. 6 Median time lag in diagnosing PFIC was 13 months to 8 years which could be attributable to poor awareness of PFIC disease spectrum among paediatricians, late referral and diagnostic difficulty.…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…17,18 As also seen in the present study, PFIC 3 presents relatively late with cholestatic symptoms developing in late infancy (1/3rd) to adolescent age group. 6 Median time lag in diagnosing PFIC was 13 months to 8 years which could be attributable to poor awareness of PFIC disease spectrum among paediatricians, late referral and diagnostic difficulty.…”
Section: Discussionsupporting
confidence: 86%
“…20 Implicating family screening, 40% of the patients of PFIC had an affected sibling or family member. Previous studies 17,18 have reported affected sibling in 15-25% of PFIC. Similar to the present study, another series 19 of 5 cases have reported all cases born at term with normal birth weight.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…[4][5][6][7][8] Mutations of ABCB11 can be found in the NHLBI ESP Exome Variant Server database (http://evs.gs.washington.edu/EVS/).…”
Section: Mutational Spectrummentioning
confidence: 99%
“…Large deletions and genomic rearrangements are also reported (10%). 3,[5][6][7][8] The majority of mutations are 'private' to specific families or ethnic communities. 5 Mutations of ATP8B1 can be found in the NHLBI ESP Exome Variant Server database (http://evs.gs.washington.edu/EVS/).…”
Section: Mutational Spectrummentioning
confidence: 99%